2013
DOI: 10.1371/journal.pone.0060143
|View full text |Cite|
|
Sign up to set email alerts
|

Characterisation of ATP-Dependent Mur Ligases Involved in the Biogenesis of Cell Wall Peptidoglycan in Mycobacterium tuberculosis

Abstract: ATP-dependent Mur ligases (Mur synthetases) play essential roles in the biosynthesis of cell wall peptidoglycan (PG) as they catalyze the ligation of key amino acid residues to the stem peptide at the expense of ATP hydrolysis, thus representing potential targets for antibacterial drug discovery. In this study we characterized the division/cell wall (dcw) operon and identified a promoter driving the co-transcription of mur synthetases along with key cell division genes such as ftsQ and ftsW. Furthermore, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 65 publications
4
56
0
Order By: Relevance
“…The phospho-MviN-FhaA complex was interpreted to regulate late stage peptidoglycan biosynthesis, thus establishing a regulatory feedback loop that can control peptidoglycan biosynthesis (54). In addition, Mur synthetases have been shown to interact with PknA and PknB (50). Based on our findings and previous data, we think that in addition to dictating PknB localization, the PASTA domainligand interaction also regulates the activity levels of PknB (23,26).…”
Section: Gsupporting
confidence: 73%
“…The phospho-MviN-FhaA complex was interpreted to regulate late stage peptidoglycan biosynthesis, thus establishing a regulatory feedback loop that can control peptidoglycan biosynthesis (54). In addition, Mur synthetases have been shown to interact with PknA and PknB (50). Based on our findings and previous data, we think that in addition to dictating PknB localization, the PASTA domainligand interaction also regulates the activity levels of PknB (23,26).…”
Section: Gsupporting
confidence: 73%
“…As cell division and PG biosynthesis genes share the dcw cluster, and that the PG biosynthetic protein PBP3 has been reported earlier to interact with both FtsW and FtsZ, therefore forming a trimeric complex in mycobacteria [26], it was hypothesized that an interaction between the PG synthesis and cell division proteins could exist. In addition to a confirmation to that, it was further reported that the regulation of mycobacterial Mur ligases were through protein-protein interactions with Ser/Thr Protein kinases and via phosphorylation [25,27].…”
Section: Target Based Approach: Validation Of Novel Therapeutic Targementioning
confidence: 77%
“…Furthermore, presence of divalent cations was found to be an absolute requirement for their activities. Also higher concentrations of ATP and UDP-sugar substrates were inhibitory for the activities of all ATP dependent Mur ligases suggesting a stringent control of the cytoplasmic steps of peptidoglycan biosynthetic pathway in M. tuberculosis [23][24][25].…”
Section: Target Based Approach: Validation Of Novel Therapeutic Targementioning
confidence: 99%
“…Dr Bhakta (Birkbeck, University of London, UK) has pioneered research in the metabolism of peptidoglycan (PG) in M. tuberculosis for over a decade. 123 The ATP dependent Mur ligase genes are involved in the synthesis of PG precursors. These genes are restricted to bacteria and have been found to be essential in mycobacteria by transposon site hybridization (TraSH).…”
Section: The Search For Novel Therapeutic Targetsmentioning
confidence: 99%